Effect of nine different exercise interventions on insulin sensitivity in diabetic patients: a systematic review and mesh meta-analysis - Pan, Yikang; Wang, Peng; Yue, Chunlin; Liu, Chen (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to assess the impact of nine exercise interventions (resistance training [BT, ball training [BT], resistance + walking [RT+W alk], resistance + running [RT + Running], resistance + cycling [RT + bicycle], running, and Tai Chi) on insulin sensitivity in patients with diabetes.MethodsA systematic search of five databases (PubMed, EMBASE, Cochrane, Web of Science, and CNKI) for RCTs investigating the effects of exercise interventions on insulin sensitivity in patients with diabetes was conducted. The quality of the included studies was assessed using the Cochrane Manual version 5.1.0 Risk of Bias Assessment Tool (ROB). Data analysis software was used for the synthesis and analysis.ResultsThis Meta-analysis comprised 21 randomized controlled trials involving 1140 participants. Cycling significantly reduced the fasting glucose index in individuals with diabetes (SUCRA score=90.7%). Resistance exercise exhibited superior efficacy in enhancing insulin sensitivity compared with alternative interventions in patients with diabetes (SUCRA score=71.8%). Furthermore, the combination of resistance exercise and running resulted in a noteworthy decrease in HOMA-IR levels (SUCRA score=64.2%).ConclusionCycling, resistance training, and combined aerobic and resistance exercises have been shown to effectively enhance fasting blood glucose levels, insulin secretion, and insulin sensitivity in individuals with diabetes. However, additional studies with longer follow-up periods and more rigorous methodologies are required to further validate these findings.Systematic review registrationhttps://ww.crd.york.ac.uk/PROSPERO/, identifier CRD42023450107.